2012
DOI: 10.4081/ijas.2012.e52
|View full text |Cite
|
Sign up to set email alerts
|

Anticatabolic activity of alpha-ketoglutaric acid in growing rats

Abstract: This study evaluated the anti-catabolic effect of a-ketoglutaric acid (AKG) in rats. Thirty Sprague Dowley male rats were divided into 3 groups of 10 animals each and fed ad libitum with protein-free diet (PFD) supplemented with 0, 3, and 6 g/kg feed of AKG for 14 consecutive days. The AKG administration had no effect on the growth performance of rats in the global trial period (0-14 d). After 7 d of excreta collection, the losses of endogenous nitrogen (N), both urinary and total, linearly reduced (P<0.05) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…In a study of growing rats, Jeevanandam et al (1991) found that diets supplemented with AKG significantly reduced N-losses. This was also demonstrated by Prandini et al (2012), who tested rats given AKG supplements of either 3 or 6 g kg −1 feed. In Atlantic salmon (Salmo salar), dietary supplementation with 5% AKG reduced N-excretions without a negative effect on vitellogenin synthesis (Olin et al, 1992).…”
Section: Q3mentioning
confidence: 64%
See 1 more Smart Citation
“…In a study of growing rats, Jeevanandam et al (1991) found that diets supplemented with AKG significantly reduced N-losses. This was also demonstrated by Prandini et al (2012), who tested rats given AKG supplements of either 3 or 6 g kg −1 feed. In Atlantic salmon (Salmo salar), dietary supplementation with 5% AKG reduced N-excretions without a negative effect on vitellogenin synthesis (Olin et al, 1992).…”
Section: Q3mentioning
confidence: 64%
“…In research with growing rats, Jeevanandam et al (1991) showed that diets supplemented with AKG helped significantly in reducing N-losses. Prandini et al (2012) also found that, when added at rates of either 3 or 6 g kg −1 of feed, AKG decreased endogenous N-losses. In Atlantic salmon, dietary supplementation with 5% AKG diminishes N-excretions (Olin et al, 1992).…”
Section: Discussionmentioning
confidence: 78%
“…More importantly, α‐KG is a precursor of some important free amino acids (FAAs) in vivo, such as glutamic acid, glutamine, proline and arginine. For instance, α‐KG can be rapidly transaminated to glutamic acid by glutamate dehydrogenase and then further aminated to glutamine by glutamine synthetase (Prandini, Morlacchini, Sigolo, & Fiorentini, ; Wang, Zhao, Jin, & Liang, ). This is an important ammonia detoxification strategy reported in many freshwater teleosts, such as the common carp ( Cyprinus carpio ), goldfish ( Carassius auratus ), African sharptooth catfish ( Clarias gariepinus ), rainbow trout ( Oncorhynchus mykiss ) and sleeper ( Bostrychus sinensis ; Anderson et al, ; Sinha et al, ; Wee et al, ; Wicks & Randall, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-ketoglutarate (AKG) is a short-chain carboxylic acid with multiple functions and is also a central molecule in the citric acid cycle (Krebs cycle). Studies have shown that AKG plays a key anti-catabolic role in growing rats and can positively interfere with N balance, thereby reducing endogenous N losses (Prandini, Morlacchini, Sigolo, Fiorentini, & Gallo, 2012). AKG has good water solubility and is non-toxic.…”
mentioning
confidence: 99%
“…This appears to be the best alternative to Gln derivatives (Xiao et al, 2016). Studies have shown that AKG plays a key anti-catabolic role in growing rats and can positively interfere with N balance, thereby reducing endogenous N losses (Prandini, Morlacchini, Sigolo, Fiorentini, & Gallo, 2012). In many tissues, including skeletal muscle, AKG is the carbon skeleton for the synthesis of Glu and Gln to improve protein status in animals (Hou et al, 2011;Hou et al, 2011;Hou et al, 2010;Blachier, Boutry, Bos, & Tome, 2009;Kristensen, Jungvid, Fernández, & Pierzynowski, 2002).…”
mentioning
confidence: 99%